El sistema defensivo de Felipe II en Cabo Verde - Ros Larena, Rosario; García Peña, Carlos (Cuadernos de Historia Moderna, 2002)
The continuous expansion of the lands of the Spanish crown made necessary to build series of fortifications in all the terrritories. It was a must to preserve the peninsular lands and it was equally important the preservation of the extend zone of the colonial empire. Many of these territories were island. One of them was the island of Santiago, in Cape Vert, with the Royal fortress of San Felipe, in Cidade Velha, the capital c ty. The text aims to approximate the reader to an estrategic place wich was many times the refuge for pirates coming from France, England and Dutch. It was one important place for slaves trade, a very relevant aspect of the economy of the area. The building of the fortress of San Felipe (c. 1585) was a part of a very wide defensive-program, for which the king Felipe II the of Spain send ingeniers and architects, among them Felipe Terzi and Joao Nunes, trained masters and inspired in the treatises of the time and learned under the Italian influence. The building of the fortress was prepared for the arriving of enemy artillery to the coast. Bastions, parapets, covereds paths..., all of them usual elements in military architecture of that time were built. The present study started in 1998. The International cooperation services made possible to know very accurtely and with a great exactitude the features of this fortresses during XVI century; this has permited a very faithful restauration of the original aspect of the monument.
Keywords: Cape Vert; Fortress of San Felipe; Cidade Velha; Ribeira Grande; Felipe II; XVI century; Felipe Terzi; João Nunes; fortification; defence; piracy; slaves